As Garantias dos Contribuintes no Âmbito do Processo Tributário - Amorim, José de Campos (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2010)
The Portuguese fiscal system integrates a set of defence mechanisms that aim at ensuring full and effective protection of the legally safeguarded interests of taxpayers in any of the stages of the fiscal process and procedure. Such administrative and judicial appeals means have the objective of preventing actions or omissions that may harm taxpayers, as well as of limiting fiscal injustice. It is also the purpose of those defence mechanisms to reinforce taxpayers rights' and to reestablish a relation of trust between taxpayers and the fiscal authorities.